Starting from the given system of equations:
![\begin{gathered} 2x-2y=-6 \\ x+6y=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gsvrbmcdnf1au7jpuavb2q83yt53434suu.png)
To solve a system by substitution, isolate one of the variables from one equation and substitute the expression for that variable on the other equation.
For instance, isolate x from the first equation:
![\begin{gathered} 2x-2y=-6 \\ \Rightarrow2x=2y-6 \\ \Rightarrow x=y-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ko6if2jlhkly4yz9srpojx9gmy6y5lflkl.png)
Substitute x=y-3 in the second equation:
![\begin{gathered} x+6y=4 \\ \Rightarrow(y-3)+6y=4 \\ \Rightarrow7y-3=4 \\ \Rightarrow7y=4+3 \\ \Rightarrow7y=7 \\ \Rightarrow y=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pf6r7ycdrkbvih74ejwqfokov5ag22xqti.png)
Then, substitute back y=1 into the expression for x:
![\begin{gathered} x=y-3 \\ \Rightarrow x=(1)-3 \\ \Rightarrow x=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ew7fb6xq69r8909y7wdck5uocyu1hahklj.png)
Therefore, the solution to the system is:
![\begin{gathered} x=-2 \\ y=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1adobemxbkz3iftkqrjfdv2pgdv6t4p03b.png)